Disciplined Seeing: Forms of Christianity and Forms of Life - Goldstone, Brian (The South Atlantic quarterly, 2010)
Drawing inspiration from Pierre Hadot and Ludwig Wittgenstein, in whose writings have been discerned a philosophical therapeutics oriented toward the cultivation of a distinctive sensibility and manner of apprehension, this essay inquires into the kinds of Christianity we see when we say that we see Christianity. We contend that, hardly the return of the repressed that it is often made out to be, the so-called turn to Christianity currently underway within the humanities and social sciences rather belongs to a much longer history of rearticulating Christianity—and subsequently “religion”—in ways commensurate with the moral, intellectual, and political determinants of a given moment. Thus grounded in a suspicion that these latest objectifications of Christianity will likewise yield images of a religiosity made uncannily legible to the disciplinary formations occupied by those who study it, our aim here is to bring about an encounter with an arguably different sort of Christianity than philosophers and anthropologists are accustomed to dealing with: namely, that displayed by Luke in his Acts of the Apostles, the first effort at depicting authoritatively the birth and character of the early Christians. Foregrounding the political and no less than theological entailments of witness that emerge from Acts, we suggest that Luke's account insinuates not only the impossibility of abstracting Christianity from the specific shape of the lives of the people who enact it, but that describing this reality might well require a remaking of the agent of investigation.